Gambaran Status Kesehatan Gingiva dan Oral Hygiene Behavior pada Pasien dengan Diabetes Melitus Tipe 2 - Adisite, Meina Nur Aeni; Pahria, Tuti; Nursiswati, Nursiswati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine gingival health status and oral hygiene behavior in patients with Type 2 DM. The method used is descriptive observational. The results showed the gingival health status in patients with Type 2 DM at RSAU dr. M. Salamun Bandung, namely, there were changes (47%), healthy (40%), and unhealthy (13%) and oral hygiene behavior in the moderate (56%) and sound (44%) categories. In conclusion, almost half of patients with type 2 DM showed changes in gingival health status with oral hygiene behavior, and most patients were in the moderate category. Keywords: Type 2 DM, Oral Hygiene Behavior, Gingival Health Status